Being a Teacher for Refugee Children: Theoretical Insights - Lunina, Simona; Jurgilė, Vaida (Acta Paedagogica Vilnensia, 2025)
The refugee crisis is not a new concept in Europe, but it has become well-known in Lithuania in the summer of 2021 when a large number of illegal migrants entered the country across the border with Belarus. According to the Illegal Migration Monitor, in 2023, 24 percent of the refugees consisted of minors. Following Russia’s invasion in Ukraine on February 24, 2022, the number of refugees across Europe increased to one million. Within the first 10 days of the Russian – Ukrainian war, 4,611 Ukrainian refugees entered Lithuania, and, according to the latest data from the Migration Department under the Ministry of the Interior of the Republic of Lithuania in 2023, 76,607 war refugees from Ukraine are registered in Lithuania. While the European education system has accrued significant experience in educating children of ethnic minorities, there is still very little research which would analyze the education of refugee children. The education of refugee and immigrant children is very different, as highlighted by Pastoor in 2016. This is the first time Lithuania has faced such an influx of refugee families with children, leading to a lack of experience and research in the education of refugee children in Lithuania. The main focus has been on the integration and socialization of refugees, with hardly any attention paid to the education of refugee children. This raises the following research questions: What are the experiences of preschool teachers working with children with the refugee status? What challenges are preschool teachers facing? How are preschool teachers working with refugee children without official descriptions prepared by the State of Lithuania?